Efficient selection and evaluation of transgenic lines of Crambe abyssinica - Li, Xueyuan; Fan, Jing; Gruber, Jens; Guan, Rui; Frentsen, Margrit; Zhu, Li-Hua (Frontiers in Plant Science, 2013)
Crambe abyssinica is a dedicated oilseed crop suitable for production of industrial feedstocks. Genetic modification of crambe has progressed substantially in the last few years, but the transformation efficiency needs to be further improved. Meanwhile, developing a reliable molecular system including Southern blot and qRT-PCR analyses is desired for effectively evaluating transgenic lines and gene expression levels of both endogenous and transgenes. In this study, we have developed an efficient transformation protocol with hygromycin as the selective agent for crambe transformation. In the regeneration test, addition of hygromycin at concentration of 5 mg L-1 resulted in 18% of shoot regeneration using crambe hypocotyls as explants, while no regeneration occurred when the hygromycin concentration reached 10 mg L-1. Based on this result, the hygromycin concentration up to 10 mg L-1 was used in the subsequent transformations. The results showed that the transformation efficiency under constant low selection pressure (H3-H3) was similar to that under higher selection pressure first followed by transfer to lower selection pressure (H10-H3). The PCR, Southern blot and fatty acid composition analyses confirmed the integration of transgenes in the crambe genome. We have also optimised the Southern and qRT-PCR methods for future studies on crambe or related species. For Southern blot analysis on crambe, more than 50 µg DNA is required for a clear band. The choice of enzymes for DNA digestion was not rigid for confirmation of the T-DNA integration, while for determining the copy number of transgenes, suitable enzymes should be chosen. Increasing the enzyme concentration could improve the digestion and 20 µl enzyme was recomended for a complete digestion of up to 80 µg crambe DNA. For qRT-PCR analysis, around 20 days after flowering was observed to be the suitable sampling time for expresseion analysis of genes invovled in the seed oil biosynthesis.